How Does Credit Default Swap Volatility Influence the Z-Score Models? - Sacadura, Jose (2018)
The literature on credit models has produced a large body of empirical research, but no consensus has emerged and scholars often disagree about the same empirical evidence. We contribute to the current literature by studying the relationship between Z-Score Models and Credit Default Swaps (CDS). The CDS provide a clean measure of risk as they are the compensation that market participants require for bearing credit default risk. We examine the CDS spreads, CDS market volatility and CDS annual performance and their relationship with Multi Discriminant Analysis Credit models (Altman’s Z-Score (1968), Z-Score’ (1983), Z-Model (1993) and Ohlson’s O-Score (1980)).Using a sample of 50 European companies and their annual CDS data available over the period 2006-2016, we find a strong negative relationship between all the credit models and the CDS market volatility and CDS market performance. We found little evidence between the models and the CDS spreads. These results suggest the notion that Credit Default Swaps have direct relevance to debtholders.